Photoelectrochemical detection for 3, 3′, 4, 4′-tetrachlorobiphenyl in fish based on synergistic effects by Schottky junction and sensitization. (1st January 2022) - Zhang, Cuizhong; Chen, Peican; Zhou, Liya; Peng, Jinyun
Highlights: The Schottky junction effect makes for enhance photoelectric conversion efficiency. The sensitization effect may be synergistically improve electron transfer. The high melting point of Au which increase the photothermal stability materials. Abstract: In this study, a novel signal amplification strategy on photoelectrochemical (PEC) aptasensor was designed for high-sensitivity and -selectivity detection of 3, 3′, 4, 4′-tetrachlorobiphenyl (PCB77) on the basis of Schottky junction and sensitization. First, the Schottky barrier not only provided an electron-transfer irreversible passage from CuO to Au Nanoparticles (NPs) but also generated excellent local surface plasmon resonance between CuO and Au NPs, thus improving the efficiency of charge separation and light absorption. Second, to further improve the response of the PEC aptasensor under the action of the sensitization, the complementary-DNA-functionalized CdS quantum dots were introduced onto the surface of CuO/Au NPs via hybridization of the target aptamer. The PEC aptasensor exhibited a low detection limit of 17.3 pg L −1, and a wide linear response was shown at a range of 0.2 – 220 ng L −1 depending on the variation of photocurrent before and after incubation.